IMPACT OF THE THERAPY WITH TUMOR NECROSIS FACTOR α INHIBITORS ON THE FREQUENCY OF UVEITIS EXACERBATIONS IN PATIENTS WITH ANKYLOSING SPONDYLITIS - Alla A Godzenko; A G Bochkova; O A Rumyantseva; I Yu Razumova; Sh F Erdes (Научно-практическая ревматология)
The course of uveitis in patients with ankylosing spondylitis (AS) does not always correlate with inflammation in the axial skeleton and peripheral joints. Effect of tumor necrosis factor α (TNFα) inhibitors on uveitis has been insufficiently studied yet, unlike their effect on the peripheral joints and spine.Objective. To compare the frequency of uveitis attacks in patients with AS during treatment with TNFα inhibitors and the conventional anti-inflammatory therapy.Materials and Methods. The study included 48 patients with AS and recurrent uveitis treated with TNFα inhibitors: 25 – infliximab, 15 – adalimumab, 9 – etanercept; 7 patients received two or more drugs sequentially. Median [25th, 75th percentiles] of the treatment duration was 3 [3.5; 5] years. The duration of treatment since the first attack of uveitis until administration of TNFα inhibitors was 5 [5; 9.7] years. Eighteen patients received only nonsteroidal anti-inflammatory drugs (NSAIDs), 30 patients received NSAIDs and basic anti-inflammatory drugs (DMARDs), including sulfasalazine (n = 23), methotrexate (n = 4), and cyclosporine (n = 4).Results. The median number of uveitis exacerbations during the standard anti-inflammatory therapy was 1 [0.4; 3] per year; during treatment with TNFα inhibitors – 0 [0; 0.5] per year (p = 0.0007). In 19 of 48 patients (40%), no exacerbations of uveitis were registered during therapy with these drugs. The frequency of uveitis attacks in patients treated with infliximab decreased from 1 [0.2; 2.75] to 0.1 [0; 0.8] episodes per year (p = 0.002), adalimumab – from 1.75 [1; 4.5] to 0 [0; 0.07] (p = 0.04), etanercept – from 0.95 [0.5; 1.75] to 0 [0; 0.07] (p = 0.001).Conclusion. Administration of TNFα inhibitors significantly reduces the frequency of uveitis attacks in patients with AS.